An evaluation of an infection prevention link nurse programme in community hospitals and development of an implementation model. Issue 1 (January 2019) - Williams, Lynne; Cooper, Tracey; Bradford, Lisa; Cooledge, Beryl; Elner, Francesca; Fisher, Denise; Huws, Jaci C; Jones, Louise; Morris, Stephanie; Rowe, Natasha; Sengwe, Robson; Roberts, Catherine; et al.
Background: Little evidence exists to show the exact impact of the link nurse role in promoting best practice in infection prevention. This paper is a report of the implementation and evaluation of a link nurse programme for community hospitals across one NHS organisation. Aim/objectives: The main aim of the study was to implement and evaluate an infection prevention link programme. The study objectives were: 1) to develop materials for a bespoke infection prevention programme which incorporated education, behaviour change, reward and recognition and 2) to evaluate the implementation of the programme, and to learn about barriers and enablers to implementation. Method: Data were collected using semi-structured telephone interviews, contact logs and online course evaluation. Data were analysed using thematic analysis. Findings: We identified four overarching themes that, collectively, construct a model for the implementation of the link nurse role in infection prevention. The themes are labelled as: selection process, support networks, essential roots, and turning points for success. Discussion: This study contributes to understanding the contribution of link nurses in infection prevention. We suggest our findings are transferable to different settings, and the model provides guidance to support future link nurse programmes and promote best practice in infection prevention practice.